Determination of Tumeric Potential for the Stabilization of Specific Mineral Elements in Two Sokoto Tomato Types - YUSUF SARKINGOBIR; HAMZA A.; GUMI A. M.; UMAR TAMBARI; A.I. UMAR (HANG TUAH MEDICAL JOURNAL, 2023)
The purpose of this work was to assess the effect of turmeric on concentrations of selected mineral elements resent in two tomato types from Sokoto state, Nigeria. Healthy, ripe and firm tomato brought from Sokoto, was selected, cleaned for this study. 5%, 10% and 25% by were dissolved in respective 5g, 10g and 25g neem extracts in 9.5, 9.0 and 7.5 liters of distilled water respectively to preserve tomatoes. The experiment was laid in completely randomized design. And elements, Na, K, Ca, Mg, and P were determined in the tomatoes after the experiment using atomic absorption spectroscopy. When Daneka tomato was observed, 2.0 to 2.5 (ppm), 3.2 to 3.7 (ppm), 2.2 to 2.6 (ppm), 0.42 to 0.46 (ppm), and 0.4510 to 0.4800 (ppm) are the respective concentrations revealed under turmeric storage method for Na, K, C, Mg, and P. The protection of concentration of different elements is dependent on the concentration of the turmeric applied in the preservation methods. 3.5 to 3.8 (ppm), 2.7 to 2.9 (ppm), 1.4 to 1.8 (ppm), 0.45 to 0.49 (ppm), and 1.2 to 1.9 (ppm) are the ranges of elements compositions of UTC tomatoes after storage under turmeric, for Na, K, Ca, Mg, and P respectively. At the end, the study has indicated, a raising concentration of elements in the all the tomato types depending on the rising turmeric concentration. Impliedly, the turmeric indicates a potential to preserve a typical quality parameter of tomatoes, that is concentration of elements at p < 0.05 significant level.